(3SdWI GdbGVj GdeOfj aj JbOjQ COdI GdEKHGJ (B:s (3OQGSI eOYeI HGLJgGOGJ GdbVGA GdLRGFQj hGdeUQj hGdaQfSj (B/s - (3ehSi, bQhas ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2020)
(3jJfGhd cJGH (B((3SdWI GdbGVj GdeOfj aj JbOjQ COdI GdEKHGJ (B: (3OQGSI eOYeI HGLJgGOGJ GdbVGA GdLRGFQj hGdeUQj hGdaQfSj(B) (3hGdPj bGe HJCdjag (B((3bQha ehSi(B) (3aj MhGdj (B(352) (3UaMI ef GdbWY GdeJhSW ; eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd JegjOj (B: (3acQI YGeI Yf GdEKHGJ GdbVGFj, GdbjQ GdHGH GdChd (B: (3SdWI GdbGVj aj COdI GdEKHGJ GdedReI, GdaUd GdChd (B: (3SdWI GdbGVj aj GdWYf HUMI GdSfO GdcJGHj, GdaUd GdKGdK (B: (3GdbGVj hGdjejf GdbVGFjI, GdaUd GdQGHY (B: (3GdaVj hGdbQGFf GdbGfhfjI, GdaUd GdChd (B: (3GdbGVj hGdTgGOI, GdaUd GdKGfj (B: (3SdWI GdbGVj aj fOH NHjQ bVGFj, GdaUd GdKGdK (B: (3SdWI GdbGVj aj ELQGA GdeYGjfI GdaUd GdQGHY (B: (3GdbGVj hGdbQGFf GdbVGFjI, Ke bGFeI GdeUGOQ hGdeQGLY GdedNUGJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B335-344.s
Keywords: (3GdSdWI GdbVGFjIs -- (3bhGfjf hJTQjYGJs -- (3aQfSGs; (3GdSdWI GdbVGFjIs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs; (3GdSdWI GdbVGFjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdCOdI GdLfGFjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdCOdI GdLfGFjIs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs; (3GdCOdI GdLfGFjIs -- (3bhGfjf hJTQjYGJs -- (3aQfSGs; (3GdEKHGJ GdLfGFjs -- (3bhGfjf hJTQjYGJs -- (3aQfSGs; (3GdEKHGJ GdLfGFjs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs; (3GdEKHGJ GdLfGFjs -- (3bhGfjf hJTQjYGJs -- (3eUQs